Characterization of Five Podoviridae Phages Infecting Citrobacter freundii - Hamdi, Sana; Rousseau, Geneviève M.; Labrie, Simon J.; Kourda, Rim S.; Tremblay, Denise M.; Moineau, Sylvain; Slama, Karim B. (Frontiers in Microbiology, 2016)
Citrobacter freundii causes opportunistic infections in humans and animals, which are becoming difficult to treat due to increased antibiotic resistance. The aim of this study was to explore phages as potential antimicrobial agents against this opportunistic pathogen. We isolated and characterized five new virulent phages, SH1, SH2, SH3, SH4, and SH5 from sewage samples in Tunisia. Morphological and genomic analyses revealed that the five C. freundii phages belong to the Caudovirales order, Podoviridae family, and Autographivirinae subfamily. Their linear double-stranded DNA genomes range from 39,158 bp to 39,832 bp and are terminally redundant with direct repeats between 183 bp and 242 bp. The five genomes share the same organization as coliphage T7. Based on genomic comparisons and on the phylogenyof the DNA polymerases, we assigned the five phages to the T7virus genus but separated them into two different groups. Phages SH1 and SH2 are very similar to previously characterized phages phiYeO3-12 and phiSG-JL2, infecting, respectively, Yersinia enterocolitica and Salmonella enterica, as well as sharing more than 80% identity with most genes of coliphage T7. Phages SH3, SH4 and SH5 are very similar to phages K1F and Dev2, infecting, respectively, Escherichia coli and Cronobacter turicensis. Several structural proteins of phages SH1, SH3 and SH4 were detected by mass spectrometry. The five phages were also stable from pH 5 to 10. No genes coding for known virulence factors or integrases were found, suggesting that the five isolated phages could be good candidates for therapeutic applications to prevent or treat C. freundii infections. In addition, this study increases our knowledge about the evolutionary relationships within the T7virus genus.